Effect of Microbial Transglutaminase on Ice Cream Heat Resistance Properties – a Short Report - Kasprzyk Iwona; Markowska Joanna; Polak Elżbieta (Polish Journal of Food and Nutrition Sciences)
The objective of this study was to investigate the effect of the addition of transglutaminase (TG) preparation Saprovia L ® (PMT TRADING Co. Ltd, Lodz, Poland) on the properties of ice cream with 40 g/kg and 70 g/kg fat content. TG was added at a concentration of 2 U/g protein. We studied the effect of transglutaminase on fresh and 3-month-stored at -25°C ice cream. Ice cream mixes were prepared with 5 g/kg stabilizer. Melting test was performed after thermal shocks until the “1st drop” occurrence. The amount of effluent was measured within the 0-120 min time frame. We evaluated the appearance of the samples and carried out the TPA and compression analysis. The addition of the enzyme has increased the resistance of stored ice cream to repeated thermal shocks.